IMPLEMENTATION OF QUALITY FUNCTION DEPLOYMENT ON E-BEKAL AS CASHLESS PAYMENT TO ENHANCE THE QUALITY OF BOARDING SCHOOL SERVICES - Hamzah, M. Fakhroni (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to determine the attributes of the E-Bekal application for students to determine the level of satisfaction of students and guardians of students using the Quality Function Deployment (QFD) method. This research uses a qualitative approach through interviews and observations to obtain technical parameter data. Furthermore, the information data on the attributes of the E-Bekal service obtained from the students and the students' guardians was analyzed using the Quality Function Deployment (QFD) model and the House of Quality (HOQ) matrix. The results of this research explain that there are priorities for developing and improving E-Bekal, namely: 1. Integration with Islamic boarding school financial systems, 2. Detailed and accurate transaction recording, 3. Implementation of strong security protocols, 4. Real-Time Transaction Notifications and Confirmations, 5. Using various commonly used payment methods. 6. Development of the NJ santri e-supply application. Penelitian ini bertujuan untuk mengetahui atribut-atribut aplikasi E-Bekal santri untuk mengetahui tingkat kepuasan santri dan wali santri dengan menggunakan metode Quality Function Deployment (QFD). Penelitian ini menggunakan pendekatan kualitatif melalui wawancara dan observasi untuk mendapatkan data parameter Teknik. Selanjutnya data informasi atribut pelayanan E-Bekal yang diperoleh dari santri dan wali santri dianalisis dengan menggunakan model Quality Function Deployment (QFD) dan matrix House of Quality (HOQ). Hasil dari penelitian ini menjelaskan bahwa terdapat prioritas pengembangan dan perbaikan E-bekal adalah sebagai berikut: 1. Integrasi dengan sistem keuangan pesantren, 2. Pencatatan transaksi secara rinci dan akurat, 3. Implementasi Protokol keamanan yang kuat, 4. Notifikasi dan Konfirmasi Transaksi secara Real-Time, 5. Memakai Berbagai Metode Pembayaran yang umum digunakan. 6. Pengembangan aplikasi e-bekal santri NJ